2021
DOI: 10.3390/genes12030353
|View full text |Cite
|
Sign up to set email alerts
|

APC Splicing Mutations Leading to In-Frame Exon 12 or Exon 13 Skipping Are Rare Events in FAP Pathogenesis and Define the Clinical Outcome

Abstract: Familial adenomatous polyposis (FAP) is caused by germline mutations in the tumor suppressor gene APC. To date, nearly 2000 APC mutations have been described in FAP, most of which are predicted to result in truncated protein products. Mutations leading to aberrant APC splicing have rarely been reported. Here, we characterized a novel germline heterozygous splice donor site mutation in APC exon 12 (NM_000038.5: c.1621_1626+7del) leading to exon 12 skipping in an Italian family with the attenuated FAP (AFAP) phe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Therefore, β-catenin levels are increased, and the expression of growth-promoting genes can be increased through downstream T-cell transcription factor (Tcf) pathways. Mutations inducing exons 12 and 13 skipping resulted in the loss of armadillo functional domains without disrupting the open reading frame, and patients carrying this variant showed a less severe FAP phenotype than patients with truncation mutations 143 .…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 98%
“…Therefore, β-catenin levels are increased, and the expression of growth-promoting genes can be increased through downstream T-cell transcription factor (Tcf) pathways. Mutations inducing exons 12 and 13 skipping resulted in the loss of armadillo functional domains without disrupting the open reading frame, and patients carrying this variant showed a less severe FAP phenotype than patients with truncation mutations 143 .…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 98%
“…It was also found that mutations in the APC led to skipping of exons or appearance of new sites of splicing [ 272 , 273 , 274 ]. Recent studies also revealed numerous novel splice sites creating mutations in cancer cells.…”
Section: Defects In Splicing and Cancermentioning
confidence: 99%